Emerging Applications and Translational Challenges for AI in Healthcare - Sidong Liu; Cristián Castillo-Olea; Shlomo Berkovsky (Information, 2024)
The past decade has witnessed an explosive growth in the development and use of artificial intelligence (AI) across diverse fields [...]